Combustion-mediated synthesis of hollow carbon nanospheres for high-performance cathode material in lithium-sulfur battery. (July 2016) - Nersisyan, Hayk H.; Joo, Sin Hyong; Yoo, Bung Uk; Kim, Dae Young; Lee, Tae Hyuk; Eom, Ji-Yong; Kim, Chunjoong; Lee, Kap Ho; Lee, Jong-Hyeon
Abstract: Hollow carbon nanospheres as potential cathode materials for lithium-sulfur (Li-S) batteries were successfully synthesized using a metathesis reaction between sodium azide and halogen polymer. The reaction was driven by thermal heat from the exothermic recombination of Na + and Cl − (or F − ) ions into NaCl (or NaF) salts. The result was an increase of the overall system temperature up to 1320–1750 °C followed by the simultaneous formation of sodium halide-carbon core–shell nanoparticles. Therefore, hollow carbon nanospheres with diameter and shell thickness of ∼50–500 nm and ∼10–50 nm, respectively, were produced after water washing of the reaction product. The composite cathode materials for Li-S batteries were manufactured by infiltrating sulfur into the hollow core of nanospheres. The electrochemical cycling showed discharge capacity of ∼700 mAh g −1 (after 100 cycles) at 0.5 C current rate which is more than ∼2.4 times larger than that for the sulfur/carbon black composites prepared by the same technique. The enhancement of battery performance was attributed to the well-organized and unique 3D structure of hollow carbon, enabling better utilization of sulfur.